One-Dimensional Simulation of Flow and Sediment Transport, A Case Study in the Aland River - Yousef Hasanzadeh; Mohammad Ali Keynejad; Kiyoumars Roushangar; Mohammad Tagi Alami (آب و فاضلاب, 2010)
In this paper, a mathematical model is presented for studying the unsteady flow, aggradation, and degradation in alluvial channels. The one-dimensional, unsteady, gradually varied flow equations (saint-venant equations) and the sediment continuity equation are solved numerically using the second-order, explicit finite difference two-step scheme developed by Lax Wendroff- Richmayer. All the three governing equations are solved simultaneously during any step so that the water flow and sediment continuity equations are coupled. The computed results are compared with the experimental results obtained in a laboratory flume. Also the Aland River data in Badalan Station with different sediment discharge equations are used for simulating the unsteady flow model bed changes and hydraulic parameters for different sections and time steps. Results show that the model is capable of simulating unsteady open channel flow, bed load transport, aggradation and degradation satisfactorily.